(untitled) (Boston, 2007)
Widely known as the anthology that best unites tradition with innovation, The American Tradition in Literature is proud to enter its fifth decade of leadership among textbook anthologies of American literature. Each volume continues to offer a flexible organization, with literary merit as the guiding principle of selection. The new photos and illustrations illuminate the texts and literary/historical timelines help students put works in context.
Keywords: American literature,Văn chương Mỹ